2021
DOI: 10.1097/mpg.0000000000002958
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Reference Values for Lean Muscle Mass in the Pediatric Patient

Abstract: Objectives: Adults with decreased muscle mass experience worse outcomes and more frequent complications. The effects of sarcopenia on pediatric outcomes are unknown. Our objective was to define reference values for lean muscle mass in a healthy pediatric population to facilitate future studies on the impact of lean muscle mass on pediatric outcomes. Patients and Methods: Bilateral psoas muscle surface area was measured by computed tomography in a health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
(50 reference statements)
0
22
1
5
Order By: Relevance
“…It is, for example, known that body weight is proportional to height cubed and not height squared during puberty [ 16 ]. In the work by Metzger et al [ 10 ], the psoas muscle index was not a linear function but was lower around the age of 8 years than in other age groups and was more pronounced in boys.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is, for example, known that body weight is proportional to height cubed and not height squared during puberty [ 16 ]. In the work by Metzger et al [ 10 ], the psoas muscle index was not a linear function but was lower around the age of 8 years than in other age groups and was more pronounced in boys.…”
Section: Discussionmentioning
confidence: 97%
“…Most reported reference values for muscle area only take age and sex into consideration, without any normalization using patient height or weight. On the other hand, a study by Metzger et al [ 10 ] and a more recent study by Somasundaram et al [ 11 ] also reported muscle indices for total psoas muscle area and total abdominal muscle area, respectively. The study by Somasundaram is especially valuable because it was performed in 2,168 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous published studies were based on a control group in this population ( 13 , 26 ), and recently Lurz et al published curves of tPMA for a Canadian population of 779 children, but did not include children under 1 year of age ( 25 ). Metzger et al published curves of tPMA in a group of 782 patients in the US and also included a small set of children under 1 year of age, but showing only p25-p50 values and no clear cut-off points ( 27 ). As we do not currently have enough abdominal CT images of healthy children under one year of age to include a control group for our population, we decided to study psoas muscle mass as a continuous variable in our statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The first handicap in our study was trying to establish a cutoff point to define sarcopenia in children under 1 year of age. Previous published studies were based on a control group in this population (13,26) (27). As we do not currently have enough abdominal CT images of healthy children under one year of age to include a control group for our population, we decided to study psoas muscle mass as a continuous variable in our statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there is emerging evidence for the use of the tPMA to determine pediatric sarcopenia as a risk factor for poor outcome in solid organ transplantation, hematologic disorders, or acute appendicitis (3,19,21,57,60). Three complementary pediatric reference values for the tPMA are currently available (10,61,62).…”
Section: Discussionmentioning
confidence: 99%